Analysis of the status of the declaration of orphan works in Europe - Arquero Avilés, Rosario; Marco Cuenca, Gonzalo (Revista General de Información y Documentación, 2016)
The European Directive 2012/28 / EU on certain permitted uses of orphan works promotes the adoption by Member States of the measures necessary to ensure that information on orphan works is recorded in a single online database for all states of the European Union. In October 2014, the European Union Intellectual Property Office (EUIPO) launched this database with the aim of collecting all relevant information about orphan works held by European cultural institutions, providing unique online access point, harmonized and transparent for the declaration of orphan works. In this context, an analysis and assessment of the current status of orphan works in Europe is presented, taking as the data source the exploitation of the public records of the European Database of Orphan Works.